Face mask recommendations in schools did not impact COVID-19 incidence among 10-12-year-olds in Finland - joinpoint regression analysis - Aapo Juutinen; Emmi Sarvikivi; Päivi Laukkanen-Nevala; Otto Helve (BMC, 2023)
Abstract Background In autumn 2021 in Finland, a recommendation to use face masks was implemented nationwide in schools for pupils ages 12 years and above. While national guidelines were in form of recommendations, cities implemented mandatory masking in schools. Some cities extended this mandate for younger pupils as well. Our aim was to compare COVID-19 incidence among 10-12-year-olds between cities with different recommendations on the use of face masks in schools. Methods COVID-19 case numbers, defined as positive laboratory verified SARS-CoV-2 test results, were obtained from the National Infectious Disease Registry (NIDR) of the Finnish Institute for Health and Welfare. Helsinki, Turku and Tampere were selected for comparison since the baseline COVID-19 incidence in the cities had been similar in August and September 2021. Helsinki and Tampere implemented the national recommendation on face mask use at schools, while Turku extended this to include those 10 years old and above, starting from the beginning of semester in early August. Age groups of 7-9-year-olds, 10-12-year-olds and 30-49-year-olds were included in the statistical analysis and moving averages of 14-day incidences per 100 000 inhabitants were used as a dependent variable. Joinpoint regression was used to estimate average percent changes (APC) and average daily percent changes (ADPC) in the 14-day incidences. Differences in the ADPC values between the cities were compared in one-month periods. We also calculated cumulative incidences from the beginning of August to the end of November in the cities by age group. Results In August, the ADPC was highest in Turku (3.9) and lowest in Tampere (2.0), while in September, the ADPC was highest in Turku (-0.3) and lowest in Helsinki (-3.2) among 10-12-year-olds. In October, the ADPC was highest in Helsinki (2.1) and lowest in Turku (-0.2) and in November, the ADPC was highest in Turku (4.1) and lowest in Tampere (-0.5) among 10-12-year-olds. We also calculated cumulative incidences from the beginning of August to the end of November in the cities by age groups of 7-9 years, 10-12 years, and 30-49 years. The cumulative incidence was highest in Turku in all age groups and lowest in Tampere. Conclusions According to our analysis, no additional effect was gained from mandating face masks, based on comparisons between the cities and between the age groups of the unvaccinated children (10-12 years versus 7-9 years).